Produktivitas Lahan Pola Lanskap Agroforestri di Desa Sumber Sari, Kecamatan Sebulu, Kabupaten Kutai Kartanegara, Kalimantan Timur - Prastiyo, Yulius Budi; Permata, Nike Dyah; Lestari, Mustika Adzania; Kurnawan, Erfin; Agustia, Monika; Indriani, Susi; Harsani; Mattaliu, Bahar (http://arl-faperta.ipb.ac.id/, 2025)
The agroforestry pattern of land use in Sumber Sari Village, Sebulu Sub District, Kutai Kartanegara District is a pattern of agrosilviculture, silvopasture and agrosilvopasture whose landscape service of land productivity value is not yet known. This research aims to analyze land productivity of agroforestry landscape pattern, focusing on factors that influence production results and sustainability of this system. The study was conducted in Sumber Sari Village, Sebulu District, Kutai Kartanegara Regency, East Kalimantan, which has an area of 3,383 ha. The research land consists of 15 lands with implementation of agroforestry landscape pattern practices by farmers which have been classified into 3 types, it’s agrisilviculture, silvopasture and agrosilvopasture. Vegetation structure and composition data from three agroforestry landscape patterns will be used to calculate plant production landscape services and land productivity (based land Equivalence Ratio [LER] value). Land use of agroforestry patterns in Sumber Sari Village, Sebulu District produces high production. Agrisilviculture pattern produces the highest production with an average production of 56.47 Mg/ha from 7 commodities. Silvopasture pattern has an average crop production of 41.33 Mg/ha from 4 commodities, while agrosilvopasture pattern has an average crop production of 33.77 Mg/ha from 6 commodities. The average LER value of land use of the agrosilvopasture pattern is slightly lower, which is 1.09 which is included in the medium category. On the other hand, LER value for land use with agrisilviculture and silvopasture patterns is greater, at 1.58 and 1.29 respectively, which are included in the high category.